(untitled) (Annals of Bangladesh Agriculture, 2025)
The fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), is globally recognized as the most destructive invasive pest of maize (Zea mays), a leading cereal crop. This study was conducted in CRD design to evaluate the antifeedant and repellant effects of four botanical oils viz. neem, castor, black cumin, and sesame on the first, second and third instars larvae. Three concentrations (5.0, 7.5, and 10%) of these oils were tested with an untreated control, and a chemical Tween-20 was used as an emulsifier. The results indicated that among the treatments, 10% castor oil exhibited the highest repellency (93.33, 88.33, and 80.00%) against the first, second, and third instar larvae, respectively, whereas 5% sesame oil showed the lowest (56.67, 40.00, and 43.33%). Repellency decreased with longer exposure periods. The 10% castor oil treatment also resulted in the lowest leaf consumption (16.67 mm2 and 77.67 mm2) and the highest mortality (20.00% and 16.67%) against the second and third instar larvae after 24 hours of exposure. The highest consumption of leaf (238.00 mm2 and 522.33 mm2) was recorded against second, and third instar larvae, respectively after 24 hours of exposure in untreated control. Considering repellency and antifeedant efficacies, the castor oil appears to be a favorable option for integration with other components of Integrated Pest Management (IPM) package against the first, second, and third instar larvae of S. frugiperda. Ann. Bangladesh Agric. 28(1): 157-165